Espacio químico de metabolitos secundarios e identificación de sus blancos terapéuticos “In Silico” en seis plantas arbóreas antibacterianas en el Perú - Vargas Ramirez, Julio James (2025)
Medicinal plants with active principles were obtained through a bibliographic review in the National Repository of Research Works (renati), and these plants are also part of the medicinal flora in Peru. Likewise, six antibacterial medicinal tree plants (Eucalyptus globulus Labill, Annona muricata, Schinus molle L., Brosimum rubescens Taubert, Anacardium occidentale, Annona cherimola) were selected, and their secondary metabolites were identified. Additionally, a chemical space analysis and the identification of their putative therapeutic targets were conducted. For this, in silico methods were used with cheminformatics software such as PUMA, DataWarrior, Anaconda Prompt, and KNIME, among others. The results included a total of 361 secondary metabolites across the six medicinal plants. It was concluded that twelve secondary metabolites showed structural similarity to three antibacterial drugs from DrugBank. Likewise, caffeic acid was identified in two of the mentioned medicinal plants. Finally, these compounds show great potential as future active molecules for therapeutic treatments.